Interactive Multimedia Learning: Innovating Classroom Education in a Malaysian University - Leow, Fui-Theng; Neo, Mai (TOJET, 2014)
This research study was conducted at INTI International University, and aimed at enhancing the quality of classroom learning for University students with three important emphases: Gagne’s instructional model, multimedia, and student-centred learning. An Interactive Learning Module (ILM) was developed as the core component in forming the multimedia-mediated student-centred learning environment (MMSLE) to improve the quality of student learning. The impacts on student learning were investigated through pre-test and post-test, questionnaires, open-ended questions and interview. A significant improvement was found in the test results, and shows that this learning environment has enhanced the students’ learning achievement. Students also show positive attitude change as they became more active and motivated in the learning process. A framework named MMSLE was proposed to provide a guideline for educators in Malaysian Universities to foster education innovations as alternatives to the conventional classroom teaching and learning methodology.